An Overview of Continuing Medical Education/Continuing Professional Development Systems in China: A Mixed Methods Assessment - Lawrence Sherman; Ming Kuang; Da-Ya David Yang; Kathy Chappell (Taylor & Francis Group, 2024)
Aims of this assessment were to describe requirements for physicians to engage in CME/CPD; explore perceptions of In-Country SMEs of their CME/CPD systems; describe perceptions of In-Country physicians about interprofessional continuing education (IPCE) and independent CME/CPD; and provide recommendations that may be adopted to improve quality and effectiveness. This assessment used a mixed-methods approach that included 1:1 interviews with in-country subject matter experts and an electronic survey capturing qualitative and quantitative data from practicing in-country physicians. This assessment reflects a country invested in the education of its physician workforce. CME/CPD systems have embedded governance structures, organizations authorized to provide education, and a recognized credit system. Governing bodies have implemented regulations to limit influence from commercial interest organizations on CME/CPD, and there is opportunity to expand delivery systems to reach physicians across diverse geographic regions, better align content to individual physicians' gaps and learning needs, and reduce cost. There is opportunity to invest in IPCE within a country with a strong professional hierarchy system. This assessment reflects CME/CPD systems that are relatively mature and identifies several opportunities to expand and enhance systems to better meet educational needs of physicians and to positively impact practice and patient outcomes.